Modified ferric trichloride water treatment agent and preparation method thereof
By introducing crosslinking agents and coagulant agents into the iron chloride treatment agent, stable chemical bonding is solved, and the problems of insufficient stability and low removal efficiency of the iron chloride treatment agent in the prior art are achieved, and a more efficient and stable water treatment effect is achieved.
Patent Information
- Application Number
- CN202510068221.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When faced with complex water quality conditions, the existing iron trichloride treatment agents have limited effect on removing heavy metal ions and low molecular weight organic matter, insufficient stability, and lack of fixation mechanisms, resulting in waste of resources and environmental pollution.
By introducing the crosslinker glutaraldehyde and the coagulant polyacrylamide, a firm chemical bond is formed between the natural porous material ferric chloride, and a composite material with stable structure and superior performance is built.
It significantly improves the stability of the material and the removal efficiency of a variety of pollutants, reduces the risk of drug loss and production costs, and is suitable for large-scale promotion and application.
Smart Images

Figure BDA0005244912390000051
Abstract
Description
Technical Field
[0001] The invention relates to the field of water treatment, and in particular to a modified ferric chloride water treatment agent and a preparation method thereof. Background Art
[0002] With the acceleration of industrialization, water pollution is becoming increasingly serious, and higher requirements are placed on efficient water treatment technology. Ferric chloride has significant advantages in water treatment, which are mainly reflected in three aspects: efficient coagulation effect, low cost and environmental protection. The iron hydroxide colloid it forms has extremely strong adsorption capacity, which can quickly condense suspended matter and impurities in the water and improve precipitation efficiency; at the same time, the price is relatively low and the dosage is small, which helps to reduce the cost of water treatment; in addition, no toxic and harmful substances are produced during the treatment process, which is environmentally friendly and in line with the concept of green chemistry. These advantages highlight the importance and application value of ferric chloride in the field of water treatment. However, in actual application, the water treatment agent disclosed in Patent No. CN101618894B has exposed shortcomings. First, its adaptability is poor. When faced with complex water quality conditions, the removal effect of pollutants such as heavy metal ions and low molecular weight organic matter is limited, and it is difficult to meet the increasingly stringent water quality standards; second, the stability of ferric chloride is insufficient, and its performance is easily affected by factors such as pH changes and temperature fluctuations, resulting in unstable performance under different environments, limiting its scope of application and reliability; in addition, due to the lack of a strong fixing mechanism, unreacted or unbound ferric chloride may be lost with the water flow, which not only causes a waste of resources, but also may cause secondary pollution and increase the environmental burden. Finally, traditional ferric chloride has a single function of sedimentation of suspended solids and cannot integrate other necessary water treatment functions, such as disinfection and deodorization, making it difficult to cope with diverse water quality treatment needs. Summary of the invention
[0003] In order to solve the technical problems of poor adaptability, insufficient stability and increased environmental burden mentioned in the above background technology, the present invention provides a modified ferric chloride water treatment agent and a preparation method thereof, which significantly improves the stability of the material and the removal efficiency of various pollutants by introducing a cross-linking agent to achieve strong chemical bonding.
[0004] The specific technical scheme of the present invention is: a modified ferric chloride water treatment agent and a preparation method thereof, comprising the following steps: 1) adding dried rice husk ash powder to a ferric chloride aqueous solution in a weight ratio of (1-1.5): (9-10), stirring thoroughly, standing, filtering, and recovering the pretreated rice husk ash; 2) adding the pretreated rice husk ash into the ferric chloride solution, stirring, adding glutaraldehyde and polyacrylamide, raising the temperature, reacting, washing, centrifuging and drying after the reaction to obtain a water treatment agent.
[0005] The present invention adopts a chemical bonding method, wherein the pretreated natural porous material and the ferric chloride solution are mixed in a specific ratio to form a composite flocculant, and a cross-linking agent is used to promote a firm bond between the two, thereby constructing a composite material with a stable structure and excellent performance. The introduction of the natural porous material significantly enhances the adsorption capacity and selectivity. In addition, due to the use of low-cost raw material straw ash and the optimization of the preparation process, the overall cost is effectively controlled, and the composite material is suitable for large-scale promotion and application.
[0006] Furthermore, in step 1), the concentration of the aqueous ferric chloride solution is 3-5%.
[0007] Furthermore, in step 1), the standing time is 24 to 30 hours.
[0008] Furthermore, in step 2), the amount of glutaraldehyde added is 0.5-2% of the mass of the ferric chloride aqueous solution.
[0009] Furthermore, in step 2), the amount of polyacrylamide added is 0.1 to 0.5% of the mass of the ferric chloride aqueous solution.
[0010] Furthermore, in step 2), the concentration of the ferric chloride solution is 3-5%.
[0011] Furthermore, in step 2), the pH value is 6 to 6.5.
[0012] Furthermore, in step 2), the reaction temperature is 30-40°C.
[0013] Furthermore, in step 2), the reaction time is 1.8 to 2.2 hours.
[0014] Furthermore, a modified ferric chloride water treatment agent prepared by the preparation method of the modified ferric chloride water treatment agent described above.
[0015] Compared with the prior art, the beneficial effects of the present invention are: 1) By introducing glutaraldehyde as a cross-linking agent, a strong chemical bond is formed between ferric chloride and the natural porous material, which greatly enhances the stability of the composite material. This not only reduces the risk of drug loss, but also ensures performance consistency under extreme conditions such as different pH values and temperatures.
[0016] 2) The large specific surface area and special structure of natural porous materials greatly improve the removal efficiency of various pollutants such as heavy metal ions and organic matter. The mild reaction conditions and simple operation steps ensure the controllability and repeatability of the preparation process and reduce production costs. DETAILED DESCRIPTION
[0017] The present invention will be further described below in conjunction with the embodiments.
[0018] Example 1 1) Preparation of initial water treatment agent Add 10g of dry rice husk ash powder to 100ml of 4% FeCl3·6H2O aqueous solution, adjust the pH of the solution to 6.0, slowly add 1g of cross-linking agent glutaraldehyde, and stir at 35°C for 2h to ensure that glutaraldehyde and the aqueous solution are fully in contact to form a stable chemical bond to obtain a preliminary water treatment agent.
[0019] 2) Post-treatment of water treatment agents 0.3 g of polyacrylamide as a coagulant aid was added to the water treatment product obtained in step 1), and after being stirred evenly, the mixture was centrifuged at 2000 r / min for 3 min to remove unreacted liquid components and collect the solid product; the solid product was washed with deionized water for two times and dried in an oven at 60° C. to obtain a modified ferric chloride water treatment agent.
[0020] 3) Performance testing The water treatment effect (turbidity removal rate, heavy metal removal rate and COD reduction rate) of the modified ferric chloride water treatment agent prepared in step 2) was tested, wherein the turbidity removal rate was tested by using a turbidity meter to measure the turbidity change of the water sample before and after treatment; the heavy metal removal rate (Cu 2+ The detection of Cu concentration is carried out by atomic absorption spectroscopy (AAS). 2+ The COD reduction rate is determined by the potassium dichromate method to determine the change in chemical oxygen demand.
[0021] Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, in step 1), 30 g of dry rice husk ash powder is added to 100 ml of 4% FeCl3·6H2O aqueous solution, and the rest of the process is the same as that of Example 1, and the specific steps are as follows: 1) Preparation of initial water treatment agent Add 30g of dry rice husk ash powder to 100ml of 4% FeCl3·6H2O aqueous solution, adjust the pH of the solution to 6.0, slowly add 1g of cross-linking agent glutaraldehyde, and stir at 35°C for 2h to ensure that glutaraldehyde and the aqueous solution are fully in contact to form a stable chemical bond to obtain a preliminary water treatment agent.
[0022] 2) Post-treatment of water treatment agents The mixture was centrifuged at 2000 r / min for 3 minutes to remove unreacted liquid components and collect solid products; the solid products were washed with deionized water for two times and dried in an oven at 60° C. to obtain a modified ferric chloride water treatment agent.
[0023] 3) Performance testing The water treatment effect (turbidity removal rate, heavy metal removal rate and COD reduction rate) of the modified ferric chloride water treatment agent prepared in step 2) is tested.
[0024] Comparative Example 2 The difference between this comparative example and Example 1 is that in this comparative example, in step 1), rice husk ash is not added to 100 ml of 4% FeCl3·6H2O aqueous solution, and the rest of the process is the same as Example 1, and the specific steps are as follows: 1) Preparation of initial water treatment agent Adjust the pH of 100 ml of 4% FeCl3·6H2O aqueous solution to 6.0, slowly add 1 g of cross-linking agent glutaraldehyde, and stir at 35°C for 2 hours to ensure that glutaraldehyde and the aqueous solution are fully in contact to form a stable chemical bond, thereby obtaining a preliminary water treatment agent.
[0025] 2) Post-treatment of water treatment agents 0.3 g of polyacrylamide as a coagulant aid was added to the water treatment product obtained in step 1), and after being stirred evenly, the mixture was centrifuged at 2000 r / min for 3 min to remove unreacted liquid components and collect the solid product; the solid product was washed with deionized water for two times and dried in an oven at 60° C. to obtain a modified ferric chloride water treatment agent.
[0026] 3) Performance testing The water treatment effect (turbidity removal rate, heavy metal removal rate and COD reduction rate) of the modified ferric chloride water treatment agent prepared in step 2) is tested.
[0027] Table 1 Effect of rice husk ash addition on the performance of modified water treatment agent Addition amount of rice husk ash / g Turbidity removal rate% Heavy metal removal rate% COD reduction rate % Example 1 10 95 90 85 Comparative Example 1 30 81 63 55 Comparative Example 2 0 83 76 72 From the data in Table 1, it can be concluded that rice husk ash, as a natural porous material, has a large specific surface area and abundant active sites, which can significantly improve the adsorption capacity of the composite flocculant. Excessive addition of rice husk ash will cause the flocs to be too loose, affecting the sedimentation performance, and at the same time causing the floc structure to be too complex, which is not conducive to the sedimentation rate and stability.
[0028] Comparative Example 3 The difference between this comparative example and Example 1 is that in this comparative example, the pH value of the FeCl3·6H2O aqueous solution is adjusted to 8, and the rest of the process is the same as that of Example 1, and the specific steps are as follows: 1) Preparation of initial water treatment agent Add 10g of dry rice husk ash powder to 100ml of 4% FeCl3·6H2O aqueous solution, adjust the pH of the solution to 8.0, slowly add 1g of cross-linking agent glutaraldehyde, and stir at 35°C for 2h to ensure that glutaraldehyde and the aqueous solution are fully in contact to form a stable chemical bond to obtain a preliminary water treatment agent.
[0029] 2) Post-treatment of water treatment agents 0.3 g of polyacrylamide as a coagulant aid was added to the water treatment product obtained in step 1), and after being stirred evenly, the mixture was centrifuged at 1000 r / min for 3 min to remove unreacted liquid components and collect the solid product; the solid product was washed with deionized water twice and dried in an oven at 60° C. to obtain a modified ferric chloride water treatment agent.
[0030] 3) Performance testing The water treatment effect (turbidity removal rate, heavy metal removal rate and COD reduction rate) of the modified ferric chloride water treatment agent prepared in step 2) is tested.
[0031] Comparative Example 4 The difference between this comparative example and Example 1 is that in this comparative example, the pH value of the FeCl3·6H2O aqueous solution is adjusted to 3, and the rest of the process is the same as that of Example 1, and the specific steps are as follows: 1) Preparation of initial water treatment agent Add 10g of dry rice husk ash powder to 100ml of 4% FeCl3·6H2O aqueous solution, adjust the pH of the solution to 3.0, slowly add 1g of cross-linking agent glutaraldehyde, and stir at 35°C for 2h to ensure that glutaraldehyde and the aqueous solution are fully in contact to form a stable chemical bond to obtain a preliminary water treatment agent.
[0032] 2) Post-treatment of water treatment agents 0.3 g of polyacrylamide as a coagulant aid was added to the water treatment product obtained in step 1), and after being stirred evenly, the mixture was centrifuged at 2000 r / min for 3 min to remove unreacted liquid components and collect the solid product; the solid product was washed with deionized water for two times and dried in an oven at 60° C. to obtain a modified ferric chloride water treatment agent.
[0033] 3) Performance testing The water treatment effect (turbidity removal rate, heavy metal removal rate and COD reduction rate) of the modified ferric chloride water treatment agent prepared in step 2) is tested.
[0034] Table 2 Effect of pH of FeCl3·6H2O aqueous solution on the performance of modified water treatment agent From the data in Table 2, it can be concluded that at a higher pH value, ferric chloride will undergo hydrolysis to form ferric hydroxide precipitate (Fe(OH)3), which not only reduces the effective Fe 3+The concentration of ions also leads to a decrease in the activity of the flocculant. At the same time, the ferric hydroxide precipitate particles are small and loose, which is not conducive to rapid sedimentation, resulting in more suspended matter remaining in the supernatant. The adsorption capacity of ferric hydroxide precipitate for heavy metal ions is limited, especially under high pH conditions. Some heavy metals will exist in the form of insoluble hydroxides, but the adsorption efficiency is low. Finally, the degradation process of organic matter may be affected, and some organic pollutants will not fully contact with the flocculant, resulting in poor removal effect; at lower pH values, although the solubility of ferric chloride increases, too low pH values may inhibit the charge neutralization and bridging effect of some pollutants, affecting the flocculation effect. The flocs are formed more slowly and the formed flocs are more compact, but may be too dense to be conducive to the effective release and adsorption of internal pollutants. Some organic pollutants may be more stable and not easily degraded or adsorbed, affecting the COD reduction rate.
[0035] Comparative Example 5 The difference between this comparative example and Example 1 is that in this comparative example, no cross-linking agent glutaraldehyde is added, and the rest of the process is the same as that of Example 1, and the specific steps are as follows: 1) Preparation of initial water treatment agent 10 g of dry rice husk ash powder was added to 100 ml of 4% FeCl3·6H2O aqueous solution, the pH of the solution was adjusted to 6.0, and stirred at 35°C for 2 h to ensure that glutaraldehyde and the aqueous solution were fully in contact to form a stable chemical bond, thereby obtaining a preliminary water treatment agent.
[0036] 2) Post-treatment of water treatment agents 0.3 g of polyacrylamide as a coagulant aid was added to the water treatment product obtained in step 1), and after being stirred evenly, the mixture was centrifuged at 2000 r / min for 3 min to remove unreacted liquid components and collect the solid product; the solid product was washed with deionized water for two times and dried in an oven at 60° C. to obtain a modified ferric chloride water treatment agent.
[0037] 3) Performance testing The water treatment effect (turbidity removal rate, heavy metal removal rate and COD reduction rate) of the modified ferric chloride water treatment agent prepared in step 2) is tested.
[0038] Comparative Example 6 The difference between this comparative example and Example 1 is that in this comparative example, the amount of cross-linking agent glutaraldehyde added is 3 g, and the rest of the process is the same as that of Example 1, and the specific steps are as follows: 1) Preparation of initial water treatment agent Add 10g of dry rice husk ash powder to 100ml of 4% FeCl3·6H2O aqueous solution, adjust the pH of the solution to 6.0, slowly add 3g of cross-linking agent glutaraldehyde, and stir at 35°C for 2h to ensure that glutaraldehyde and the aqueous solution are fully in contact to form a stable chemical bond to obtain a preliminary water treatment agent.
[0039] 2) Post-treatment of water treatment agents 0.3 g of polyacrylamide as a coagulant aid was added to the water treatment product obtained in step 1), and after being stirred evenly, the mixture was centrifuged at 2000 r / min for 3 min to remove unreacted liquid components and collect the solid product; the solid product was washed with deionized water for two times and dried in an oven at 60° C. to obtain a modified ferric chloride water treatment agent.
[0040] 3) Performance testing The water treatment effect (turbidity removal rate, heavy metal removal rate and COD reduction rate) of the modified ferric chloride water treatment agent prepared in step 2) is tested.
[0041] Table 3 Effect of pH of the amount of cross-linking agent added on the performance of the modified water treatment agent Addition amount of cross-linking agent / g Turbidity removal rate% Heavy metal removal rate% COD reduction rate % Example 1 1 95 90 85 Comparative Example 1 0 72 64 55 Comparative Example 2 3 77 68 57 As shown in Table 3, when the amount of cross-linking agent added is too small, the number of chemical bonds formed is limited, and it is unable to fully promote the strong bond between ferric chloride and natural porous materials. In practical applications, it is easy to increase the risk of agent loss and reduce the overall treatment effect. Due to the weak bond, the composite materials may not be able to fully exert their respective advantages, and the adsorption capacity and selectivity are reduced. Excessive addition of cross-linking agent will lead to excessive cross-linking, making the composite material too dense and rigid. The formed flocs are too tight and the internal voids are reduced, which is not conducive to the effective contact and adsorption of pollutants. At the same time, overly dense flocs may cause the sedimentation rate to slow down, and more suspended matter will remain in the supernatant. Finally, unreacted cross-linking agent may remain in the product, causing potential secondary pollution risks, especially at high concentrations. Glutaraldehyde itself has certain toxicity.
[0042] Comparative Example 8 The difference between this comparative example and Example 1 is that in this comparative example, polyacrylamide as a coagulant aid is not added, and the rest of the process is the same as that of Example 1, and the specific steps are as follows: 1) Preparation of initial water treatment agent Add 10g of dry rice husk ash powder to 100ml of 4% FeCl3·6H2O aqueous solution, adjust the pH of the solution to 6.0, slowly add 1g of cross-linking agent glutaraldehyde, and stir at 35°C for 2h to ensure that glutaraldehyde and the aqueous solution are fully in contact to form a stable chemical bond to obtain a preliminary water treatment agent.
[0043] 2) Post-treatment of water treatment agents The water treatment agent obtained in step 1) is centrifuged at 2000 r / min for 3 minutes to remove unreacted liquid components and collect solid products; the solid products are washed with deionized water for two times and dried in an oven at 60° C. to obtain a modified ferric chloride water treatment agent.
[0044] 3) Performance testing The water treatment effect (turbidity removal rate, heavy metal removal rate and COD reduction rate) of the modified ferric chloride water treatment agent prepared in step 2) is tested.
[0045] Comparative Example 9 The difference between this comparative example and Example 1 is that in this comparative example, the amount of polyacrylamide added as a coagulant aid is 1 g, and the rest of the process is the same as that of Example 1, and the specific steps are as follows: 1) Preparation of initial water treatment agent Add 10g of dry rice husk ash powder to 100ml of 4% FeCl3·6H2O aqueous solution, adjust the pH of the solution to 6.0, slowly add 1g of cross-linking agent glutaraldehyde, and stir at 35°C for 2h to ensure that glutaraldehyde and the aqueous solution are fully in contact to form a stable chemical bond to obtain a preliminary water treatment agent.
[0046] 2) Post-treatment of water treatment agents 1 g of polyacrylamide as a coagulant is added to the water treatment product obtained in step 1), and after being stirred evenly, the mixture is centrifuged at 2000 r / min for 3 min to remove unreacted liquid components and collect solid products; the solid products are washed with deionized water twice and dried in an oven at 60° C. to obtain a modified ferric chloride water treatment agent.
[0047] 3) Performance testing The water treatment effect (turbidity removal rate, heavy metal removal rate and COD reduction rate) of the modified ferric chloride water treatment agent prepared in step 2) is tested.
[0048] Table 4 Effect of pH of coagulant addition on the performance of modified water treatment agent Addition amount of coagulant / g Turbidity removal rate% Heavy metal removal rate% COD reduction rate % Example 1 0.3 95 90 85 Comparative Example 1 0 61 53 50 Comparative Example 2 1 73 32 56 From the data in Table 4, it can be concluded that if the amount of coagulant added is too little, the floc structure formed is not tight enough, the sedimentation rate slows down, the treatment time is prolonged and it is easy to loosen. Due to the instability of the flocs, more suspended matter remains in the supernatant, the transparency is reduced, and the sewage treatment efficiency is reduced. If the amount of coagulant added is too much, the flocs will be excessively aggregated and form overly dense clumps, resulting in a reduction in internal voids, which is not conducive to the effective contact and adsorption of pollutants and slows down the sedimentation rate. Unreacted coagulant may remain in the product, causing potential secondary pollution risks.
[0049] Example 2 1) Preparation of initial water treatment agent Add 15g of dry rice husk ash powder to 100ml of 3.5% FeCl3·6H2O aqueous solution, adjust the pH of the solution to 6.0, slowly add 0.5g of cross-linking agent glutaraldehyde, and stir at 35°C for 2h to ensure that glutaraldehyde and the aqueous solution are fully in contact to form a stable chemical bond to obtain a preliminary water treatment agent.
[0050] 2) Post-treatment of water treatment agents 0.3 g of polyacrylamide as a coagulant aid was added to the water treatment product obtained in step 1), and after being stirred evenly, the mixture was centrifuged at 2000 r / min for 3 min to remove unreacted liquid components and collect the solid product; the solid product was washed with deionized water for two times and dried in an oven at 60° C. to obtain a modified ferric chloride water treatment agent.
[0051] 3) Performance testing The water treatment effect (turbidity removal rate, heavy metal removal rate and COD reduction rate) of the modified ferric chloride water treatment agent prepared in step 2) was tested, wherein the turbidity removal rate was tested by using a turbidity meter to measure the turbidity change of the water sample before and after treatment; the heavy metal removal rate (Cu 2+ The detection of Cu concentration is carried out by atomic absorption spectroscopy (AAS). 2+ The COD reduction rate is determined by the potassium dichromate method to determine the change in chemical oxygen demand.
[0052] Example 3 1) Preparation of initial water treatment agent Add 9 g of dry rice husk ash powder to 100 ml of 4% FeCl3·6H2O aqueous solution, adjust the pH of the solution to 6.0, slowly add 2 g of cross-linking agent glutaraldehyde, and stir at 35°C for 2 h to ensure that glutaraldehyde and the aqueous solution are fully in contact to form a stable chemical bond to obtain a preliminary water treatment agent.
[0053] 2) Post-treatment of water treatment agents 0.1 g of polyacrylamide as a coagulant aid is added to the water treatment product obtained in step 1), and after being stirred evenly, the mixture is centrifuged at 2000 r / min for 3 min to remove unreacted liquid components and collect solid products; the solid products are washed with deionized water twice and dried in an oven at 60° C. to obtain a modified ferric chloride water treatment agent.
[0054] 3) Performance testing The water treatment effect (turbidity removal rate, heavy metal removal rate and COD reduction rate) of the modified ferric chloride water treatment agent prepared in step 2) was tested, wherein the turbidity removal rate was tested by using a turbidity meter to measure the turbidity change of the water sample before and after treatment; the heavy metal removal rate (Cu 2+ The detection of Cu concentration is carried out by atomic absorption spectroscopy (AAS). 2+ The COD reduction rate is determined by the potassium dichromate method to determine the change in chemical oxygen demand.
[0055] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0056] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a modified ferric chloride water treatment agent, characterized in that: The following steps are involved: 1) adding dried rice husk ash powder to an aqueous solution of ferric chloride in a weight ratio of (1-1.5):(9-10), stirring thoroughly and then standing to obtain pretreated rice husk ash; 2) Add glutaraldehyde to the pretreated rice husk, raise the temperature, and react. After the reaction, add polyacrylamide, stir evenly, wash, centrifuge, and dry to obtain a water treatment agent.
2. A method for preparing a modified ferric chloride water treatment agent according to claim 1, characterized in that, In step 1), the concentration of the ferric chloride aqueous solution is 3-5%.
3. A method for preparing a modified ferric chloride water treatment agent according to claim 1, characterized in that, In step 1), the standing time is 24 to 30 hours.
4. A method for preparing a modified ferric chloride water treatment agent according to claim 1, characterized in that, In step 2), the amount of glutaraldehyde added is 0.5-2% of the mass of the ferric chloride aqueous solution.
5. A method for preparing a modified ferric chloride water treatment agent according to claim 1, characterized in that, In step 2), the amount of polyacrylamide added is 0.1-0.5% of the mass of the ferric chloride aqueous solution.
6. A method for preparing a modified ferric chloride water treatment agent according to claim 1, characterized in that, In step 2), the concentration of the ferric chloride solution is 3-5%.
7. A method for preparing a modified ferric chloride water treatment agent according to claim 1 or 6, characterized in that, In step 2), the pH value is 6 to 6.
5.
8. A method for preparing a modified ferric chloride water treatment agent according to claim 1, characterized in that, In step 2), the reaction temperature is 30-40°C.
9. A method for preparing a modified ferric chloride water treatment agent according to claim 1, characterized in that, In step 2), the reaction time is 1.8 to 2.2 hours.
10. A modified ferric chloride water treatment agent prepared by the method for preparing a modified ferric chloride water treatment agent according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of ferric chloride
CN101618894B
Preparation method of modified expanded rice husk spherical adsorption material
CN107159151A
Adsorption treatment method for heavy metal ion-containing wastewater
CN107337249A
Composite treating agent for comprehensively removing heavy metals in electroplating wastewater
CN109384277A
Microbial compound deodorant and preparation method thereof
CN109529526A